Design of Functional Safety for Process Automation by Considering the Justification of Cost - Benefit Using ALARP Evaluation Method - Teerawat Thepmanee; Pornpatchara Khamkoon (My University, 2016)
This paper addresses the design of functional safety for process automation in accord with IEC 61508/ 61511 standard. Functional safety design of a tail gas treating unit has been conducted in this study. The average probability failure on demand was calculated using fault analysis and then used as the criterion for the safety instrumented function design in order to conform the required safety integrity level (SIL). The result reveals that the architecture of safety instrumented function, the test interval, and the test method made a significant impact on improving the average probability of failure on demand (PFD avg ) of the process. In addition, the cost-benefit evaluation was justified from asset & production loss consequence using As Low As Reasonably Practicable (ALARP) method in order to determine justification for the additional investment of the high SIL against the given additional risk reduction.
Keywords: IEC 61508; Safety instrumented system; Management and Optimization Techniques